The Impact of Financial Innovation, Product Innovation and Institution Innovation on Banks’ Financial Performance in the UAE: Evidence from CS-ARDL - Sara Ibrahim Saleem Alnusair,; Tajul Ariffin Masron,; Abdul Saqib,; Haslindar Ibrahim, (Asian Academy of Management Journal of Accounting and Finance, 2025)
In today’s competitive market, innovation is vital for long-term bank success. This study addresses a research gap by examining how financial, product and institution innovations impact the performance of the United Arab Emirates (UAE) banks. We adopted a new quantitative index to measure financial innovation, using information technology and employee training hours as proxies for institution innovation, while product innovation is uniquely assessed by total deposits through mobile banking applications. This study examines the impact of these innovations on the financial performance of UAE banks, differentiating between high-performing and low-performing banks as well as large and small banks. Using CS-ARDL modelling to analyse the data, we found that financial innovation positively impacts the financial performance of UAE banks across all subgroups. However, financial and institution innovations have a greater impact on high-performing and large banks than on low-performing and small banks, which often struggle with limited resources and expertise. Conversely, product innovation tends to significantly boost financial performance in lower-performing and small banks. This is because high-performing banks often face difficulties with new products in saturated markets, while large banks grapple with managing complex operations and extensive asset bases. These findings imply that choosing the right types of innovation can significantly improve bank performance.